Dating the Renaming of Cities Referred to in the Biblical Conquest and Settlement Accounts - Naʾaman, Nadav (Vetus Testamentum, 2021)
The article systematically examines the historicity of the biblical claim that the Israelites renamed several Canaanite cities in the course of the conquest and settlement of the land. Among the renamed places are Kiriath-arba, Kiriath-sepher/ sannah, Kerioth-hezron, Zephath, Jebus/the Jebusite, Luz, Laish, Kenath, and Argob. Examination of the renaming claim of these towns only confirms the Late Bronze date of Laish and possibly Zephath. All other ostensibly Canaanite city names must have emerged only during the Iron Age. The article further examines the antiquity of the name Baʿal(ah)/Kiriath-baʿal of Kiriath-jearim and suggests that it emerged in the first millennium BCE. Evidently, the renaming claim in biblical literature is entirely literary and ideological; only few interchanges of names reflect authentic memories of the toponymy of Canaan in the Late Bronze Age.